What motivates the Malaysian workforce : content and process - Azhar Ahmad (2005)
If human resources are to be effectively utilized, management has to understand what motivates employees. While motivation research has produced some solid evidence in the western world, little is known about what motivates their counterparts in developing countries especially Malaysia. This MM project paper aims to explore the responsiveness of Malaysian workforce with varying ethnical cultures values to work motivation concepts. This research is beneficial in understanding the key motivating factors for Malaysians to improve work satisfaction and productivity. In order to empirically test the work motivation content and process effectiveness in the Malaysian settings, this study has developed a cultural-based work motivation model. The research instrument developed with local contents as its major focus, built upon (i) organizational behavior's cultural dimensions concepts; and (ii) work motivation theories from both content and process approaches. Based on mean responses, the rank order of work motivation content factors in descending importance is: (i) financial rewards; (ii) recognition; (iii) good working conditions; (iv) growth and promotion opportunities; and (v) achievement needs. The data analysis suggested that Malaysian employees are generally responsive to most work motivation processes. Finding showed (i) correlation between motivational factors and ethnic values; and (ii) employee's demographic profile influences the motivation inclination. The evidence suggested further research area into the comparative study of the foreign and local work motivation needs to clearly determine cross-cultural implications on work motivation theories.